Psychopathy and Intimate Partner Violence - Cunha, Olga (Journal of interpersonal violence, 2021)
Several studies found that psychopathy is an important predictor of criminal behavior in general and of intimate partner violence in particular. However, these conclusions are often based on scales with less well-established validity, and some inconsistent results have emerged with regard to the contribution of specific psychopathic facets to intimate partner violence. In a sample of 152 batterers from Portugal aged between 22 and 70 years old, we examined whether Psychopathy Checklist–Revised (PCL-R) total scores and the four facets (scored based on a semistructured interview and on file information) predicted the frequency of intimate partner violence. Two separate linear regression analyses were conducted controlling for criminal variables. PCL-R total scores positively predicted intimate partner violence frequency, above and beyond the criminal variables. As for the four facets, only the PCL-R affective facet held a significant effect in predicting intimate partner violence frequency after controlling for criminal variables. These results support the inclusion of psychopathy in risk assessments and treatment of perpetrators of intimate partner violence, particularly with regard to the affective deficits of the construct.